EXPERIENCES OF ENGLISH LANGUAGE FACULTY MEMBERS OF A PUBLIC UNIVERSITY IN KAZAKHSTAN REGARDING DIGITAL LEARNING PLATFORMS INTEGRATION IN HIGHER EDUCATION - Akhmetkaliyev, Aibek (Nazarbayev University Graduate School of Education, 2025)
This study investigates faculty perceptions regarding digital learning platforms integration in higher education in Kazakhstan by drawing on data collected through qualitative research methods. Though initiatives such as “Digital Kazakhstan” seek to modernize the teaching and learning, there exists a huge gap between the policy and the real class practice. This research adopts a qualitative case study design of experiences of English language faculty members of a public university in the north of Kazakhstan. From their attitudes, the challenges they faced in adopting DLPs and the strategies they employed, their attitudes were explored through semi- structured interviews. The interview data were analyzed thematically, and key benefits (benefited from enhanced teaching efficiency, improved student engagement and flexibility of learning modalities) and the critical barriers (poor infrastructure unreliability training, and resistance to change) were identified. Based on Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology, this study concludes that ease of use, usefulness, and robust institutional support are factors of faculty adoption decision. This confirms that to achieve DLP integration, ongoing professional development, tackling digital inequalities and bridging the gap between high level aspirations and actual conditions should be considered. This thesis contributes to the local discourse of the digitalization of higher education and global conversations related to the use of technology for inclusive and student-centered learning by providing context specific insights and recommendations. Keywords: digital learning platforms, higher education, Kazakhstan, faculty perceptions, Technology Acceptance Model
Keywords: Type of access: Open